Quantitative analysis of bioactive compounds in five black tea sortiments of the romanian market - Popoviciu, Dan Răzvan; Bădin, Mihaela Valentina (Bangladesh Journal of Botany, 2024)
Five black tea types, Assam, Darjeeling, Earl Grey, English Breakfast and Oolong were tested for their chlorophyll, carotenoid, flavonoid, total phenolic content and essential oil content. English Breakfast had the highest chlorophyll content (834 mg/kg) and Earl Grey, the highest carotenoid content (360 mg/kg). Total phenolic content was the highest in Darjeeling (an average of 40,874 mg/kg ), while flavonoids, specifically, reached the highest concentrations in Oolong (498 mg/kg). Total essential oils were maximum in Assam tea blend (4,600 mg/kg). Tea pH values ranged between 6.13-6.66. Bangladesh J. Bot. 53(3): 555-560, 2024 (September)